Dear Mr. Brody [videorecording (DVD)] - Brody, Michael, Jr (Greenwich Entertainment, 2023)
When 21-year-old hippie millionaire Michael Brody Jr. decided to give away his fortune to anyone in need, he ignited a psychedelic spiral of events. An instant celebrity, Brody was mobbed by the public, scrutinized by the press, and overwhelmed by the crush of personal letters responding to his extraordinary offer. Fifty years later, an enormous cache of these letters is discovered unopened.